The role of rank-ligand inhibition in the treatment of postmenopausal osteoporosis - M. Varenna; D. Gatti (Reumatismo, 2011)
Osteoporosis is a skeletal disease affecting millions of people worldwide in which a decreased bone mass and a microarchitectural deterioration compromise bone strength leading to bone fragility and increased susceptibility to fracture. Bone turnover increases at menopause, with osteoclast-mediated bone resorption exceeding bone formation. Recent discoveries in bone biology have demonstrated that RANKL, a cytokine member of the tumor necrosis factor superfamily, is an essential mediator of osteoclast formation, function and survival. Denosumab is a fully human monoclonal antibody with a high affinity and specificity for human RANKL. By binding to its target, denosumab prevents the interaction of RANKL with its receptor RANK on osteoclasts and their precursors and inhibits osteoclast-mediated bone resorption. Administered as a subcutaneous injection every six months, denosumab has been shown to decrease bone turnover and to increase bone mineral density in postmenopausal women with low bone mass and osteoporosis. In these patients denosumab significantly reduced the risk of vertebral fractures, hip fractures and nonvertebral fractures. In all clinical trials published to date, denosumab was well tolerated with an incidence of adverse events, including infections and malignancy, generally similar to subjects receiving placebo or alendronate. The denosumab therapeutic regimen consisting in a subcutaneous injection every 6 months may increase patient compliance and persistence with a further benefit from treatment. By providing a new molecular target for osteoporosis treatment, denosumab is a promising drug for the treatment of postmenopausal osteoporosis and the prevention of fragility fractures.